Individual’s Core Competences in the Innovation Process: A Proposal of Personality Profiles Required in Each Innovation Stage - Mariela Martinez; Manon Enjorlas; Laure Morel (Journal of Technology Management & Innovation, 2023)
Models of the innovation process, such as open innovation, lean innovation, disruptive innovation, and others, have been developed these last years to improve organizational innovation. However, limited studies exist focused on identifying the individual’s competences related to the stages of the innovation process, even though, they (the individual competences) have been considered the starting point of the innovation process and are part of the different factors that could impact favourable outcome of those models. This study aims then to identify the individual’s core competences of the leaders of the innovation process, required to efficiently handle the specificities of each innovation stage. The importance of this proposal is strengthened by the fact that by understanding its competences (skills, traits, and behaviors) within the innovation process, the human capital could be strategically placed, trained, and optimize it impact. It has the potential to significantly enhance the innovation performance of an organization.